Report on capacity building in the scaling of drought-tolerant varieties, RiceAdvice app, mechanization, and climate information services in Mali - Suh, Neville; Diallo, Aboubacar; Diarra, Ba Afoussatou; Minindiou, Samuel; Dossou-Yovo, Ronald (2024)
The increased vulnerabilities of resource-poor farm communities to climatic stressors and unpredictable weather patterns continue to pose a substantial threat to agriculture, affecting the livelihood and well-being of farm households in Mali. Climate-smart agricultural (CSA) practices and Climate Information Services (CIS) technologies are crucial to strengthening vulnerable farm households and communities’ resilience to climate threats, improving their productivity, food security, and income. In collaboration with local partners and actors in Mali, the AICCRA Mali cluster, a project supported by the World Bank, organized a capacity-building workshop on CSA and CIS technologies to contribute to climate resilience in Mali. The two-day capacity-building workshop registered 29 participants (10% female) from 12 organizations. Participants included lead farmers from agricultural cooperatives, extension agents, researchers from government and non-government organizations, and other actors engaged in climate change issues in the rice value chain from Sikasso, Segou, and Koulikoro regions. This report presents the progress made from the capacity-building initiative to promote the scaling of CSA and CIS technologies in Mali. Specifically, the training workshop covered several CSA and CIS technologies: (i) CIS, the different platforms and the type of information available to farmers; (ii) Drought-tolerant rice varieties, the yield of these varieties and resistance to biotic and abiotic stressors; (iii) Agricultural mechanization and RiceAdvice, an agricultural business model used for increasing rice productivity and yield. Participants expressed strong intentions of sharing the insightful knowledge acquired with other actors in their communes and villages. Other participants, such as lead farmers from cooperatives, were also committed to applying the new knowledge gained to their farms.